Analysis of the Relationships of Industrial Work Practices, Knowledge, and Entrepreneurship Readiness: A Study of Tourism Vocational School Student Competency in Developing Tour Travel Packages - Irni Istiqomah; Suparji; Marniati (Indonesia Approach Education, 2022)
Study aims to describe and analyze the factors that influence the entrepreneurial readiness of Tourism Vocational Schools in East Java in the skills to arrange travel packages for overland routes and for more than one day. This type of research is ex post facto research with path analysis testing techniques. Data collection techniques using observation methods, giving written tests and questionnaires. Data analysis was carried out using descriptive, measurement model, and structural analysis. To stakeholders in entrepreneurship learning and travel business expertise competencies to further improve the quality and quantity of their learning so that vocational students have a more reliable quality of work readiness. The importance of teaching entrepreneurship in the SMK curriculum and its relevance in the subject curriculum. A review of the current provision for entrepreneurship in subject programs suggests that despite the substantial inclusion of the topic in the program, there may be potential for course teams that currently do not offer this aspect to consider reasons for its inclusion in their curricula.